3(x-2)+3=3(2x-8)

Simple and best practice solution for 3(x-2)+3=3(2x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)+3=3(2x-8) equation:



3(x-2)+3=3(2x-8)
We move all terms to the left:
3(x-2)+3-(3(2x-8))=0
We multiply parentheses
3x-(3(2x-8))-6+3=0
We calculate terms in parentheses: -(3(2x-8)), so:
3(2x-8)
We multiply parentheses
6x-24
Back to the equation:
-(6x-24)
We add all the numbers together, and all the variables
3x-(6x-24)-3=0
We get rid of parentheses
3x-6x+24-3=0
We add all the numbers together, and all the variables
-3x+21=0
We move all terms containing x to the left, all other terms to the right
-3x=-21
x=-21/-3
x=+7

See similar equations:

| 30=13u-7u | | 3s+9s+10s=16 | | 17x+4-3x=8-10x+44 | | 5=q-75/4 | | 3-(x-1)=25 | | 7d+d=4d-7=5d | | 41=3x+9 | | -3y+19=y-3 | | 11-2t=3 | | 9+2x=5x+18 | | 5g+3=5 | | 15x+3+18x-6=90 | | 9=p/4+5 | | 1500=x(120-2x) | | 4x-2/6+3+x/4=1/2 | | 460+g=11(g) | | 5(p+1)=2p+11 | | 9^x-3=8 | | 15x+3+18x-6=180 | | F+4/6g=6g | | 5(+1)=2p+11 | | |x+17|+10=70 | | 6+7v+3v=v+8v | | a−12.9=29.4 | | 5/p=15/7 | | x/7-20=-10 | | 8m+3-m=19 | | -4x-9=5x+10x+10 | | 95+x+x=180 | | -41+7+2n=1 | | P^2-13=-12p | | 2z+5(z-1)=3z-1 |

Equations solver categories